1981
DOI: 10.1084/jem.153.5.1225
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Igh-linked gene products on the generation of T helper cells in the response to sheep erythrocytes.

Abstract: The role of Igh-linked loci in the generation and expression of T cell help for antibody responses to sheep erythrocytes (SRBC) was investigated. The production of IgM, IgG3, IgG1, IgG2b, and IgG2a antibody to SRBC was shown to be T cell dependent. The Igh-congenic mouse pair CBA/Tufts (Ighj) and CBA.Ighb gave equivalent responses to SRBC. CBA.nude mice (Ighj) supplemented with peripheral T cells of either Ighj or Ighb genotype produced equivalent, high responses. Therefore, T cell-B cell mismatching for the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1982
1982
1994
1994

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…There have been several reports suggesting that the Igh locus influences the selection of the T-cell repertoire (Nutt et al 1981;Seman and Zilberfarb 1979;Monguini and Paul 1982;B6naroch et al 1993). T cells can recognize B-cell idiotypes, especially those that are highly cross-reactive (Hetzelberger and Eichmann 1978;Gleason and K6hler 1982).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been several reports suggesting that the Igh locus influences the selection of the T-cell repertoire (Nutt et al 1981;Seman and Zilberfarb 1979;Monguini and Paul 1982;B6naroch et al 1993). T cells can recognize B-cell idiotypes, especially those that are highly cross-reactive (Hetzelberger and Eichmann 1978;Gleason and K6hler 1982).…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of isotype regulation has been described by Herzenberg and co-workers (1982). The subclass response to SRBC has been shown to be influenced by the Igh locus gene products (Nutt et al 1981), and in the C57B10 mouse may be mediated by suppressor T cells (Seman and Zilberfarb 1979). It has also been suggested that isotype switching can be influenced by cytokine production by non-T cells (Snapper and Mond 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of Igh-C or linked gene products on the generation of helper cells involved in allotype-or isotype-specific responses has been demonstrated in several systems. The existence of a helper cell specifically committed to help Iglb memory cells, but distinct from carrier-primed Thl, was shown by , and experiments by L'Age Stehr (1981) and Nutt et al (1981) have demonstrated Igh-Iinked restriction between B and primed T cells in responses to SRBC antigens. In the latter cases however Thl and Tig were not distinguished.…”
Section: Evidence For Helper Cell Heterogeneity In Other Systemsmentioning
confidence: 94%
“…In animals, T helper cells with specificity for allotypes, idiotypes, and isotypes have all been demonstrated (24)(25)(26). In mice, the allotype regulation ofthe antibody response to sheep erythrocytes has been demonstrated to be mediated through T cell help (27).…”
Section: Km(j) Allotype and Heavy Chain Specific Responsementioning
confidence: 99%